A Simple and Portable Reader to Analyze Concentration of Iron in Blood Plasma via Colorimetric Analysis - M.Soair, Siti Nur’Arifah Binti; Tan, Arthur Foo Yen; Yap, Boon Kar (International Journal of Engineering and Technology, 2018)
This paper presents a simple and portable body iron reader to analyze the concentration of iron via colorimetric analysis. Through this approach, early diagnosis can be made for diseases such as iron deficiency anemia (IDA) and thalassemia. The uses of spectrophotometer to analyze a concentration of analyte in a sample can be reconsidered. Spectrophotometer nowadays is bulky and very expensive. The proposed portable reader can gives the user a result of concentration of analyte in a sample solution almost the same as the commercially available spectrophotometer. Through a comparison, the portable body iron reader managed to obtain a 0.9986 coefficient of determination value which has only 0.13% of error. Moreover, this device can works with a battery without the needs of power source. Â